Construção em falsa cúpula na região transfronteiriça Gerês-Xurés: metodologias e caracterização - Barroso, Carlos E. (2018)
Although underestimated during decades, vernacular heritage is today understood as an important and fundamental piece of the identity by different civilizations. In the context of the European society that has lost its links and references to its original identity, vernacular architecture has gained importance due to its authenticity and the rediscover of its economic potential in the growing markets for the natural and rural environmental tourism. Although its importance, today this abandoned and damaged heritage is at risk because of rural exodus and the vanishing of traditional ways of life. The vernacular corbelled dome shepherds' constructions, settled in brandas and currais, are a testimony of the past rural and livestock traditional way of life of the Geres-Xures region, recognized by UNESCO has a World Biosphere Reserve. To study this important heritage, a research project was undertaken. The main objectives and the research methodology are presented in this paper, as well as the main outputs obtained so far.